Pengaruh Metode Belajar Practice Rehearsal Pairs Terhadap Peningkatan Keterampilan Handstand - Firdaus Hendry Prabowo Yudho; Rahmat Iqbal; Citra Resita; Nana Suryana Nasution; Abdul Kholik (UNIVERSITAS NEGERI MAKASSSAR, 2022)
This study aims to investigate the influence of Practice Rehearsal Pairs learning methods on improving handstand skills performed in blended learning situations with a total of 12 sessions, of which 6 sessions are conducted online and 6 sessions offline. The research method used is quasi-experiments with a sample number of 31 people. Research data is obtained by comparing the means of wall handstand test at the beginning and end of the study. The descriptive and inferential analysis is conducted to get the results of the average test from the different samples. The conclusion of this study is that there are insignificant differences in the post and pre results of handstand skill tests through Practice Rehearsal Pairs on gymnastic learning materials.